AB1076 The usefulness of high-resolution ultrasonography of the first metatarsophalangeal joint in acute gout. (23rd January 2014) - Moon, K.; Kang, M.; Jeon, Y.; Kim, J.
Abstract : Background: The first metatarsophangeal (MTP) joint is most commonly involved joint in acute gout. The gout is often diagnosed by clinical findings, not arthrocentesis, especially in the first MTP joint. Various non-invasive methods to diagnose gout have developed until now. High-resolution ultrasonography has recently been raised as a promising new imaging modality for gout. We intended to find out characteristic sonographic features of acute gouty arthritis involving the first MTP joint, and evaluated the efficacy and safety of ultrasound-guided intraarticular steroid injection. Objectives: The aims of this study are first, to identify the characteristic sonographic findings of acute gouty arthritis affecting the first MTP joint in comparison to non-affected MTP joint, and second, to evaluate the efficacy and safety of ultrasound-guided intraarticular steroid injection to the first MTP joint. Methods: We enrolled 20 patients with acute gouty arthritis involving the first MTP joint unilaterally, performed a sonographic evaluation for both (affected and non-affected) first MTP joints, and compared the sonographic features of affected joint with non-affected one. Ultrasound-guided intraarticular steroid (triamcinolone 10mg and 2% lidocaine 1ml) was injected to the affected first MTP joint in 16 patients. Visual analogue scales (VAS) for pain, general disability, walking disability were assessed at baseline, 24 hrs, 48 hrs, and 7 days after injection. Results: Bone erosion, joint effusion, synovial hypertrophy, double contour sign in ultrasonography were not significantly different in both (affected and non-affected) first MTP joints, but more tophus-like lesion was present (p<0.01), and higher power doppler signal was observed in affected joint (p=0.037). The reduction of mean VAS scores in pain, general disability, walking disability were 49.9 mm (±27.0), 33.7 mm (±26.3), 39.4 mm (±27.1), respectively, at 48hrs after ultrasound-guided intraarticular steroid injection. There were no serious adverse events. Conclusions: More prevalent tophus-like lesion and higher power doppler signal in high-resolution ultrasonography are characteristic features of acute gout compared to non-affected joint. Ultrasound-guided intraarticular steroid injection to the first MTP joint is an effective and safe therapeutic option. References: Thiele RG, Schlesinger N. Diagnosis of gout by ultrasound. Rheumatology 2007;46:1116–.1121 Wright SA, Filippucci E, McVeigh C, Grey A, McCarron M, Grassi W, et al. High-resolution ultrasonography of the first metatarsal phalangeal joint in gout: a controlled study. Ann Rheum Dis 2007;66:859–864. Perez-Ruiz F, Naredo E. Imaging modalities and monitoring measures of gout. Current Opinion in Rheumatology 2007;19:128–133. Gerster JC, Landry M, Dufresne L, Meuwly JY. Imaging of tophaceous gout: computed tomography provides specific images compared with magnetic resonance imaging and ultrasonography. Ann Rheum Dis 2002;61:52–54 Fernández C, Noguera R, González JA, Pascual E. Treatment of acute attacks of gout with a small dose of intraarticular triamcinolone acetonide. J Rheumatol 1999;26(10):2285-6. Disclosure of Interest: None Declared